The last stage of informalism in Costa Rica with Superviviencia (1971) from Lola Fernández Caballero (1926-) - Montero Rodríguez, Daniel Adolfo (2019)
The present article consists in a semiotic study of the Costa Rican painting during the decade of the seventies in the 20th century, as well as the end of the non-figuration painting, and with a special emphasis on the informalism present in “Supervivencia” (1971) from artist Lola Fernández. Methodologically speaking, we turn to the semiotic analysis of the artistic text, through a gradual process of interpretation of the sign in three levels (syntactic, semantic and pragmatic). Furthermore, both notions of "informalism" and "abstract art" are conceptualized in this article using a theoretical approach. In addition, this study will refer to the socio-historical context of the I Bienal Centroamericana de Pintura (First Central American Painting Biennial), which took place in 1971. As a result of the previously stated approaches, we will be able to determine how the verdict of the Bienal propelled the Costa Rican non-figuration painting movement to come to an end. Likewise, we disclose refentialities in “Supervivencia” (1971) that were either never seen before, or were maybe omitted by the art critics of that time. Received: 02-20-2019 Approved: 03-29-2019